Meta-Analisis Intervensi Berbasis Parent Training Untuk Meningkatkan Efikasi Kompetensi Orangtua dengan Anak ADHD - ALISHA; Yudiarso, Ananta (Inquiry: Jurnal Ilmiah Psikologi, 2024)
This study was conducted to present and determine whether Parent Training (PT) based intervention programs were effective to improve parent’s sense of competence efficacy in handling and managing their children’s disrupting ADHD symptoms. PT is an alternative that has been proven effective to improve children’s condition diagnosed with ADHD, although the effect on parents’ competence of parenting is worth discussing, notably parents as the children’s companion and their function as a family. This study of meta-analysis consisted of a total of 1434 participant from 11 studies as comparison with medium effect size as the result (Hedges g) 0.398 (95% Cl = 0.292 to 0.503) related to the PT effectiveness is not quite significant to improve parents’ sense of competence in managing their children’s disrupting ADHD symptoms.